METABOLIC SYNDROME: ASSESSMENT OF QUALITY OF LIFE, ANXIETY AND DEPRESSION IN PATIENTS - Moskalenko, O. L.; Smirnova, O. V.; Kasparov, E. V.; Kasparova, I. E. (Siberian Journal of Life Sciences and Agriculture, 2021)
Rationale. The article examines the assessment of the quality of life, psychological state (anxiety-depressive disorders, neurosis-like states) in patients with metabolic syndrome. The prevalence of metabolic syndrome in different countries is 25-30% and varies depending on the criteria used. The severity of the clinical manifestations of the metabolic syndrome affects the quality of life of patients, while the indicators of physical and mental health decrease. The problem of the quality of life of patients suffering from overweight and obesity is relevant and socially significant. Obesity leads to anxiety-depressive disorders, neurosis-like states, which contributes to a worsening of the prognosis of the underlying disease. The number of patients with chronic metabolic disorders (obesity, type 2 diabetes mellitus, non-alcoholic fatty liver disease) is increasing in the world every year. The aim of our work was to assess the quality of life, the level of anxiety and depression in patients with metabolic syndrome. Materials and methods. The authors presented the results of a study of 60 patients with metabolic syndrome and 45 apparently healthy volunteers. Examination of patients, determination of anthropometric indicators with an assessment of the quality of life (questionnaire SF-36) were carried out. The level of anxiety and depression was determined according to the hospital scale of anxiety and depression HADS. Statistical processing of the obtained data was carried out using the application package “STATISTICA 8.0”. Results. Most of the quality of life indicators were statistically significantly different in patients with metabolic syndrome relative to the control group. There was a decrease in the average level of the parameters “physical functioning” by 17.3%, “role functioning” by 31%, “general health” by 11.3%, “vitality” by 13%, “emotional functioning” by 50.1%. … The level of anxiety and depression in patients with metabolic syndrome corresponded to the subclinical level, the level of depression exceeded the value of the control group by 18%. Conclusion. The study shows that patients with metabolic syndrome are characterized by a decrease in quality of life indicators, subclinically severe anxiety / depression. The goal of any treatment, according to MAPI Research Institute specialists, is to improve the quality of life of patients to the level of healthy individuals, therefore, for patients with metabolic syndrome, along with pathogenetic therapy aimed at reducing body weight, correction of psychological disorders is required, which will reduce the level of anxiety-depressive disorders and will improve quality of life indicators.
CRIS-Team Scopus Importer:2023-04-20
Keywords: anxiety-depressive disorders; metabolic syndrome; obesity; quality of life